Foreign and Russian practices of research and diagnosis of the gerontological ageism phenomenon - I. V. Sokolova (Вестник университета, 2023)
The development of foreign and Russian scientific psychological theories of gerontological ageism brings this problem to a new level: new approaches to determining the essence of ageism are developing, new methods and models of diagnosis, prevention and assistance in gerontological discrimination are emerging. The purpose of the article is a comparative analysis of domestic and foreign practices of studying the phenomenon of gerontological ageism. The reliability of the research results is confirmed by the theoretical analysis of scientific literature, comparative analysis of Russian and foreign scientific literature. The author attempts to periodize the development of foreign theory and practice of countering gerontological ageism. The Russian periods of development of psychological science explaining the problems of ageism are analyzed. The main conclusion is a comparative analysis of the causes and factors of gerontological discrimination.